Porcine reproductive and respiratory syndrome prevalence and processing fluids use for diagnosis in United States breeding herds - Kikuti, Mariana; Vilalta, Carles; Sanhueza, Juan; Melini, Claudio Marcello; Corzo, Cesar A. (Frontiers in Veterinary Science, 2022)
Processing fluids have been recently adopted by the U.S. swine industry as a breeding herd PRRS monitoring tool due to its increased representativeness of animals within the herd. Here, we use the Morrison Swine Health Monitoring Project (MSHMP) database, representative of approximately 50% of the U.S. swine breeding herd, to describe processing fluids submissions for PRRS diagnosis and its relation to PRRS prevalence and time to stability over time between 2009 and 2020. We illustrate that processing fluids diagnosis submissions increased starting in 2017, around which time the overall PRRS prevalence seasonal pattern changed. The difference between each year’s highest and lowest weekly prevalence averaged 10.9% between 2009 and 2017, whereas it averaged 5.0% in 2018-2020 period. Each year’s lowest weekly prevalence ranged from 11.3% to 19.5% in 2009-2017 and from 22.4% to 29.2% in 2018-2020. We also detected an increasing proportion of breeding sites that did not reach stability within one year of reporting an outbreak (chi-square for trend p<0.0001). The total time to stability was not associated region of the country the site was located, site’s air filtration status, PRRS status before the outbreak, or the different statuses a site achieved to be classified as stable, when accounting for production system in the multivariable model. However, a higher proportion of system-wide processing fluids use was associated with increased time to stability. Altogether, the temporal concurrence of processing fluids used for PRRS virus monitoring suggests that the adoption of this sampling strategy may help explain the changes observed in PRRS status 1 prevalence since 2018, although further studies are still needed.